ANALISIS FAKTOR-FAKTOR PENENTU PERSISTENSI LABA (Studi Empiris Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2016) - KhoirulAmaliyah, 13.05.52.0063; Suwarti, Titiek (Students' Journal of Accounting and Banking, 2018)
This study examines the effect of cash flow volatility, accruals, sales volatility, debt level, operating cycle and firm size to earnings persistence. This research is conducted at Indonesia Stock Exchange by using unit of analysis of manufacturing company which have go public. Sampling method using purposive sampling with research period 2014-2016. Relationship and or influence between variables explained by using multiple analysis method with program SPSS 19. The results showed that the sales volatility, debt level and operating cycles had a significant effect. While volatility of cash flow, the amount of accruals and firm size have no effect to earnings persistence.Keywords: Volatility of cash flow, accrual amount, sales volatility, debt level, operating cycle, firm size and profit persistence.